2019
DOI: 10.1111/1756-185x.13562
|View full text |Cite
|
Sign up to set email alerts
|

Influence of disease duration and socioeconomic factors on the prevalence of infection and hospitalization in rheumatoid arthritis: KRAC study

Abstract: Aim: The use of healthcare resources by rheumatoid arthritis (RA) patients can be related to the presence of disease, comorbid conditions, use of steroids, and the combined use of immunosuppressants. This study evaluated the risk factors associated with infection and hospitalization in RA. Methods: This multicenter, cross-sectional study enrolled 3247 RA subjects fulfilling the 2010 American College of Rheumatology/European League Against Rheumatism criteria to examine the prevalence of hospitalization and epi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 26 publications
(25 reference statements)
0
3
0
Order By: Relevance
“…Subsequent data from the FORWARD database demonstrated that 5.9% of patients with RA treated with TNF inhibitors, non-TNF inhibitors, bDMARDs (abatacept, rituximab, tocilizumab and anakinra) or csDMARDs (n = 11,623) experienced an SI during 27,552 patient-years of follow-up [89]. Studies from other parts of the world reinforce the association between RA and the increased burden of infection, with studies from the UK and India reporting that between 3% and 8% of patients with RA experience infections (Table 3) [90,91]. A diagnosis of RA may also increase infection risk in a surgical setting, with a retrospective, US-based case-control study (n = 2212) reporting that RA was associated with a 47% increased risk of postoperative infection following total joint arthroplasty vs. patients with osteoarthritis (odds ratio (OR): 1.47; p = 0.031) [92].…”
Section: Effect Of Ra Treatments On CV Riskmentioning
confidence: 96%
See 1 more Smart Citation
“…Subsequent data from the FORWARD database demonstrated that 5.9% of patients with RA treated with TNF inhibitors, non-TNF inhibitors, bDMARDs (abatacept, rituximab, tocilizumab and anakinra) or csDMARDs (n = 11,623) experienced an SI during 27,552 patient-years of follow-up [89]. Studies from other parts of the world reinforce the association between RA and the increased burden of infection, with studies from the UK and India reporting that between 3% and 8% of patients with RA experience infections (Table 3) [90,91]. A diagnosis of RA may also increase infection risk in a surgical setting, with a retrospective, US-based case-control study (n = 2212) reporting that RA was associated with a 47% increased risk of postoperative infection following total joint arthroplasty vs. patients with osteoarthritis (odds ratio (OR): 1.47; p = 0.031) [92].…”
Section: Effect Of Ra Treatments On CV Riskmentioning
confidence: 96%
“…A number of patient demographics and comorbidities have been shown to be predictive of the observed increased risk of infection in patients with RA [86]. Factors associated with an increased infection risk include male sex [92,93,96], older age [90,93,95,96,110,111], longer RA disease duration [90,93], a history of SIs [88], lower education [90], family income [90], rural residency [88], geographical location [111], poor nutritional status [112] and higher BMI [111]/obesity [92]. Significantly increased infection risks have been described for patients with comorbid conditions including renal dysfunction [93,95,113], pulmonary disease [89], underlying lung disease [93,112] and diabetes [88,92,111].…”
Section: Comorbidities As a Risk Factor For Infection In Patients With Ramentioning
confidence: 99%
“…As the one of the most common inflammatory arthritis affecting about 1% of world population [ 1 , 2 ], rheumatoid arthritis (RA) is associated with an increasing socioeconomic impact and often affects the diarthrodial joints, including knee joint [ 3 , 4 ]. Total knee arthroplasty (TKA) is considered one of the most effective orthopedic health care interventions for patients with rheumatoid arthritis (RA) [ 5 8 ], and RA patients achieve better satisfaction after TKA compared to patients with osteoarthritis (OA) [ 8 ].…”
Section: Introductionmentioning
confidence: 99%